Epstein‐Barr virus‐associated primary central nervous system cytotoxic T‐cell lymphoma. Issue 4 (21st December 2012) - Ogura, Ryosuke; Aoki, Hiroshi; Natsumeda, Manabu; Shimizu, Hiroshi; Kobayashi, Tsutomu; Saito, Tomohisa; Takizawa, Jun; Okamoto, Kouichirou; Hasegawa, Go; Umezu, Hajime; Ohshima, Kouichi; Takahashi, Hitoshi; et al.
Abstract : Primary central nervous system lymphoma (PCNSL) expressing T‐cell markers is rare, among which nasal‐type extranodal NK/T‐cell lymphoma is an extremely rare subtype associated with Epstein‐Barr virus (EBV) infection. Here we report the clinicopathologic features of a case of EBV‐associated PCNSL showing a cytotoxic T‐cell phenotype. The patient, a 73‐year‐old woman, presented with rapidly progressive mental deterioration. Brain MRI revealed multiple lesions with swelling in the bilateral cerebral hemispheres, which were hypointense on T1‐weighted images, hyperintense on T2‐weighted and fluid‐attenuated inversion recovery images, and slightly hyperintense on diffusion‐weighted images. Biopsy specimens from the temporal region showed many medium‐sized anaplastic lymphocytic cells with perivascular and angio‐invasive patterns in the cortex. Immunohistochemically, the cells were positive for CD3, CD8, T‐cell‐restricted intracellular antigen‐1 (TIA‐1), granzyme B and perforin, but negative for CD56 and CD20. In situ hybridization revealed EBV‐encoded RNAs in the tumor cell nuclei. A rearrangement study showed T‐cell receptor γ–chain gene rearrangement with a clonal appearance. The patient died 6 months after surgery, and a general autopsy revealed no lymphoma cells outside the brain. These cellular profiles are inconsistent with those of extranodal NK/T‐cell lymphoma, and have not been previously described. This case appears to represent an unusual CNS manifestation of EBV‐associated T‐cell lymphoma.